PABRA Database - Pan-Africa Bean Research Alliance (2014)
The Pan African Bean Research Alliance (PABRA) database is a project of the Pan African Bean Research Alliance, which is a network of 29 collaborating Sub-Saharan African Countries and is facilitated by the International Center for Tropical Agriculture (CIAT) working alongside the National Agricultural Research Systems (NARS), the National Agricultural Statistical Services (NASS), local and international NGOs, input industries; Community based organizations, and other key stakeholders. Organized according to the PABRA program outcome areas (breeding, seed systems, integrated crop management, capacity building, nutrition, Data Synthesize and marketing), the PABRA database is an initiative of the Monitoring, Evaluation and learning unit in PABRA. It is one of the most outstanding developments drawing out of the monitoring and evaluation work in PABRA in the period 2004 and 2014. Almost twenty three years of bean research work in Africa can be sourced from this database. This database was motivated by a long term PABRA interest to ensure that partners have access to performance related information originally acquired from them through monitoring data capture efforts. The objective of the knowledge database is to promote use of data, carry out cross country comparisons, inform good practices & learning and enhance opportunity to replicate and scale out. The database is presented alongside skills and knowledge building in order to promote ease of access and use.